2020
DOI: 10.1093/infdis/jiaa389
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Rapid Diagnostic Tests for Hepatitis C Virus With or Without HIV Coinfection: A Multicentre Laboratory Evaluation Study

Abstract: Abstract Background Hepatitis C virus (HCV) screening is critical to HCV elimination efforts. Simplified diagnostics are required for low-resource settings and difficult-to-reach populations. This retrospective study assessed performance of rapid diagnostic tests (RDTs) for detection of HCV antibodies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Beijing, China) and the First Response HCV card test (Premier Medical Corporation Ltd., Mumbai, India). Operational characteristics of these tests are shown in S1 Table. These RDTs were selected as they met WHO prequalification criteria in archived plasma samples in the previous study [7], and the manufacturers had demonstrated a commitment to seeking WHO prequalification status.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Beijing, China) and the First Response HCV card test (Premier Medical Corporation Ltd., Mumbai, India). Operational characteristics of these tests are shown in S1 Table. These RDTs were selected as they met WHO prequalification criteria in archived plasma samples in the previous study [7], and the manufacturers had demonstrated a commitment to seeking WHO prequalification status.…”
Section: Methodsmentioning
confidence: 99%
“…RDTs were tested on three sample types: fingerstick whole blood, ethylenediaminetetraacetic acid (EDTA) plasma, and serum (matched samples), all collected and tested on the same day. Performance was compared with three WHO prequalified laboratory reference tests, of which two were enzyme immunoassays (EIAs; Murex Anti-HCV version 4.0, Fujirebio INNOTEST HCV Ab IV) and one was a line immunoassay (LIA; Fujirebio INNO-LIA HCV Score), using a previously described composite reference standard (CRS) that incorporated the results of all three reference tests [7]. The algorithm was based on WHO prequalification evaluation protocols, with the final decision being based on the LIA test result.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations